Copy art y electrografía - Gracia, Silvio de 1973-; Bleus, Guy 1950-; Tenke, István; Held, John 1947- (Hotel DaDa editor, 2021)
DISCONTINUED journal specialized in mail art and visual poetry, edited and directed by mailartist, visual poet and performer Silvio De Gracia (Junín, Argentina 1973), who in 2020, founded, together with the performer and experimental poet Ana Montenegro, the art gallery Hotel DaDa Base de Arte Correo y Poesía Experimental. Only 18 issues were published (between 2002 and 2021) and each of them is thematic, addressing different topics of mail art and experimental poetry were addressed, such as mail art and new technologies, artistamps, rubberstamps, action poetry, collages, copy art and electrography, as well as tributes to figures such as Ray Johnson and Edgardo Antonio Vigo and to the 100 years of the DADA movement. HOTEL DADA, located in the city of Junín, in the northwest of the province of Buenos Aires, is a gallery specialized in mail art and experimental poetry.
Keywords: Geschichte 1938-2021; Kopiegraphie; Elektrofotografie; Lateinamerika